Case report: Focal segmental glomerulosclerosis and nephrotic syndrome following treatment with pamidronate for calcitriol toxicity - Dawson, Katherine Ann; Blong, April; Walton, Rebecca (Frontiers in Veterinary Science, 2022)
Abstract Objective: To describe a case of glomerulosclerosis resulting in nephrotic syndrome following administration of pamidronate disodium to treat clinical calcitriol toxicity in a dog. Case Summary: A 12-week-old intact male Labrador Retriever weighing 11.8 kg presented with lethargy and vomiting 20 hours after ingesting a 100 g tube of topical antipsoriatic cream (3 mcg/g of calcitriol)a. Severe hypercalcemia was present on the day of presentation. Hypercalcemia treatments such as saline diuresis, furosemideb, and dexamethasone sodium phosphatec were initiated. The dog was also administered a single dose of pamidronate disodiumd on the day of presentation. Initially the patient’s clinical signs improved, and the hypercalcemia resolved. One-hundred and thirty hours post-pamidronate disodiumc administration the patient developed biochemical abnormalities and severe edema, consistent with nephrotic syndrome and was euthanized. Necropsy results revealed evidence of focal segmental glomerulosclerosis. Unique Information: Pamidronate disodium, commonly used for treatment of hypercalcemia, may have resulted in glomerulosclerosis and nephrotic syndrome in a dog with calcitriol toxicity. This complication should be taken into consideration when monitoring patients treated with pamidronate disodium for hypercalcemia.